2022
DOI: 10.3390/socsci11100450
|View full text |Cite
|
Sign up to set email alerts
|

Siberian Cedar in Russian Business Naming: A Case Study

Abstract: Business naming is important in the modern economy, but it can differ between countries. This makes it urgent to pay attention to representative examples of business naming (to be distinguished from brand naming) from different countries. This case study focuses on the usage of Siberian cedar in the names of Russian firms. This huge tree from taiga forests is not a true cedar, but pine. The national database permits the identification of 87 organizations named after Siberian cedar. Their geographical distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The spaces in which they plied their trade were eradicated or repurposed, and the emerging "reasonable" and "ordered" spaces-hawker centers-were increasingly policed, cleaner, and more orderly at every turn" (Tarulevicz 2018b, p. 175). Ermolaev and Ruban (2022) distinguish between business and brand names; in the former, the former is more important to businessmen, while the latter are more important to customers. It is also worth noting that previous research has looked at how branding can be used in both consumer (Chan and Huang 2001) and industrial products (Shipley and Howard 1993), although the distinctions between business and brand names tend to be unclear, and hence, the difference as outlined by Ermolaev and Ruban is useful.…”
Section: A Brief History Of Hawking In Singaporementioning
confidence: 99%
See 1 more Smart Citation
“…The spaces in which they plied their trade were eradicated or repurposed, and the emerging "reasonable" and "ordered" spaces-hawker centers-were increasingly policed, cleaner, and more orderly at every turn" (Tarulevicz 2018b, p. 175). Ermolaev and Ruban (2022) distinguish between business and brand names; in the former, the former is more important to businessmen, while the latter are more important to customers. It is also worth noting that previous research has looked at how branding can be used in both consumer (Chan and Huang 2001) and industrial products (Shipley and Howard 1993), although the distinctions between business and brand names tend to be unclear, and hence, the difference as outlined by Ermolaev and Ruban is useful.…”
Section: A Brief History Of Hawking In Singaporementioning
confidence: 99%
“…Likewise, Liesch et al (2015) reported that business names in Michigan follow regional-naming practices and geographical boundaries. Meanwhile, many Russian firms name their businesses after the Siberian cedar, even if they are not necessarily located in Siberia, and are in industries that do not use the tree as a raw material (Ermolaev and Ruban 2022). The authors postulate that the tree is associated with positive connotations such as stability and power, which bodes well for businesses and, at the same time, is aligned with the "stereotypical vision" of Siberia in Russian culture-one characterized by cold weather and enigmatic taiga forests where cedars grow (Ermolaev and Ruban 2022, p. 6).…”
Section: Business Namesmentioning
confidence: 99%